A necessary and sufficient condition for Walrasian social choice. - Nagahisa, Ryo-ichi (Journal of Economic Theory, 1994)
The writer discusses Walrasian resource allocations in terms of social choice axioms, each of which reflects concepts of collective rationality, ethical considerations, and/or informational constraints. Drawing on Debreu-Scarf's core convergence theory, he argues that the Walras rule is the only rule satisfying the core property, non-discrimination, generalized monotonicity, and local decisiveness.